BUDGET IMPACT ANALYSIS OF BELIMUMAB IN TREATING SYSTEMIC LUPUS ERYTHEMATOSUS. (5th December 2016) - Pierotti, Francesca; Palla, Iaria; Pippo, Lara; Lorenzoni, Valentina; Turchetti, Giuseppe
Abstract : Objectives: The study evaluates the costs of systemic lupus erythematosus (SLE) and the budget impact due to the introduction of belimumab in the Italian setting. Methods: Adaptation to the Italian setting of a budget impact model with a time horizon of 4 years (year 0 without belimumab, years 1–3 with belimumab) to compare treatment, administration, and clinical monitoring costs of standard therapy and of the alternative scenario in which belimumab is administered in addition to the standard therapy to the subgroup of patients selected according to the label approved by the European Medicines Agency. The model takes also into account the costs of flares. Results: Over 3 years, belimumab is able to prevent cumulatively 1, 111 severe flares and 3, 631 nonsevere flares with a total saving for the Italian National Health System (NHS) of approximately €6.2 million. Budget impact ranges from €4.4 million in the first year to €20.3 million in the third year. Conclusions: The decrease in the number of flare partially counterbalances the costs of the new technology (impact attenuation of approximately 16 percent). These data elucidate the importance to control and monitor the disease progression and to prevent exacerbations, which are the major causes of the increase in costs paid by the NHS and by the society. The financial impact could be replicate on a regional basis, to inform local decision makers. Further developments are possible as the model does not consider the additional clinical and economic benefits of reduced damage accrual and slowed disease progression.